P16 Pre-screening in patients with IBD, a positive single centre quality improvement project. (19th June 2022) - Colclough, James; Ali, Mohamed; Shami, Nafe; Aitchison, Lucy; Hurst, Anne; Shams-Khan, Hafsa
Abstract : Introduction: Biologic and immunomodulator therapies are required in the majority IBD patients' treatment journeys. These therapies are associated with increased risk of opportunistic infections and malignancies. BSG guidance 1 outlines the necessary investigations required before starting these treatments. We assessed our compliance with these guidelines before and after implementing a proforma led SOP to evaluate whether there was any improvement in clinical practice. Method: A pre-screening checklist proforma was created for all IBD patients starting biologics or immunomodulators at Southport and Ormskirk hospital and compliance with BSG guidelines was measured before and after its implementation. Data was collected retrospectively using electronic patient records over two 12-month cycles; pre-implementation (Nov 2018 – Oct 2019) and post-implementation (Feb 2020 – Jan 2021). Results: 55 patients (50.1% female, median age 48, range 19-84) were started on treatment before the proforma was implemented and 68 after (48.5% female, median age 43, range 17-83). Screening tests for baseline bloods and opportunistic infections improved from 68% to 100% with the largest improvements in Hepatitis B and TB screening (biologics only). Checking of vaccination and cervical screening improved from 1% to 74.6% and 7% to 70.4% respectively. Conclusion: The introduction of a pre-screening checklist for patients starting on biologic or immunomodulator therapies improved our compliance with BSG guidelines from 1% to 70.4%, therefore improving patient safety prior to starting these treatments. This data compares favourably with national audit data where only 60% of patients had adequate pre-screening 2 . It has allowed us to standardise care in screening for contraindications to treatment, especially opportunistic infections. There is still room for improvement when assessing patients' vaccination and cervical screening histories, however these rely on documentation of the discussion in notes and may underestimate the number of patients receiving this advice. Overall we have shown a dramatic improvement in the pre-screening service that we offer to our IBD patients starting biologic or immunomodulator therapies. We will continue to use the checklist as well as educating other staff about the importance of pre-screening for improving patient safety. References: Lamb CA, et al. British Society of Gastroenterology consensus guidelines on the management of inflammatory bowel disease in adults. Gut 2019;68: s1-s106. Arnott I, et al. 2016. National clinical audit of biological therapies – Annual report 2016 .